2021
DOI: 10.1038/s41392-021-00679-0
|View full text |Cite|
|
Sign up to set email alerts
|

The signal pathways and treatment of cytokine storm in COVID-19

Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic has become a global crisis and is more devastating than any other previous infectious disease. It has affected a significant proportion of the global population both physically and mentally, and destroyed businesses and societies. Current evidence suggested that immunopathology may be responsible for COVID-19 pathogenesis, including lymphopenia, neutrophilia, dysregulation of monocytes and macrophages, reduced or delayed type I interferon (IFN-I) response, antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
470
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 440 publications
(488 citation statements)
references
References 376 publications
(324 reference statements)
14
470
0
4
Order By: Relevance
“…Cytokine storm, hyperinflammation, multiorgan failure, and acute respiratory distress syndrome were described in COVID-19 patients with high fever, dyspnea, lymphopenia, and high serum ferritin, D-dimers, C-reactive protein (CRP), and cytokines, including IL-1b, IL-6, and TNF-α [ 31 , 32 ]. Several studies showed that the severity of COVID-19 symptoms positively correlated with blood levels of proinflammatory cytokines and chemokines (e.g., IL-1b, TNF-α, monocyte chemoattractant protein 1 [MCP-1], MCP-3, cytosolic carboxypeptidase 2 [CCL2], CCL3, IL-2, sIL-2RA, IL-6, IL-7, IL-17, IL-18, granulocyte colony-stimulating factor [G-CSF], interferon gamma-induced protein 10 [IP10], macrophage colony-stimulating factor [M-CSF], and microprotein 1a [MIP-1a]) and anti-inflammatory cytokines (e.g., IL-10) [ 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: The Immunology Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Cytokine storm, hyperinflammation, multiorgan failure, and acute respiratory distress syndrome were described in COVID-19 patients with high fever, dyspnea, lymphopenia, and high serum ferritin, D-dimers, C-reactive protein (CRP), and cytokines, including IL-1b, IL-6, and TNF-α [ 31 , 32 ]. Several studies showed that the severity of COVID-19 symptoms positively correlated with blood levels of proinflammatory cytokines and chemokines (e.g., IL-1b, TNF-α, monocyte chemoattractant protein 1 [MCP-1], MCP-3, cytosolic carboxypeptidase 2 [CCL2], CCL3, IL-2, sIL-2RA, IL-6, IL-7, IL-17, IL-18, granulocyte colony-stimulating factor [G-CSF], interferon gamma-induced protein 10 [IP10], macrophage colony-stimulating factor [M-CSF], and microprotein 1a [MIP-1a]) and anti-inflammatory cytokines (e.g., IL-10) [ 33 , 34 , 35 , 36 , 37 , 38 ].…”
Section: The Immunology Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…Various other cytokines, such as G-SCF or GM-CSF, and a variety of chemokines such as IL-8, MCP-1, MIP1α, and MIP1β found to be elevated in acute COVID-19 patients [ 18 ] are also known to activate the JAK/SAT3 pathway [ 88 , 92 ]. The enhanced transcription of JAK/STAT3 activators, such as IL-6 and multiple chemokines (including IL-8, MCP-1, MIP1α, and MIP1β), found during acute respiratory viral infections, including also SARS-CoV-2, is largely triggered also by NF-κB pathway activation [ 38 , 93 , 94 ].…”
Section: Sars-cov-2 Spike Protein Subunit S1 Induces Jak/stat3 Activationmentioning
confidence: 99%
“…Thus, targeting macrophages is suggested as a therapeutic option for COVID-19 infection [ 135 ]. Hence, using anti-inflammatory pharmaceuticals along with applying TTFields can be a solution for this challenge [ 136 138 ]. However, the role of macrophages in COVID-19 is a controversial area [ 139 , 140 ].…”
Section: Tumor Treating Fields Its Benefits and Covid-19mentioning
confidence: 99%